2003
DOI: 10.1097/01.ccm.0000060446.45080.c6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of polyacrylonitrile (AN69) and polysulphone membrane during hemofiltration in canine endotoxic shock

Abstract: In this acute endotoxic shock model, CVVH with the polyacrylonitrile membrane improved cardiac performance when compared with the polysulphone membrane. These effects could be caused by a more effective adsorption of inflammatory mediators other than tumor necrosis factor. Whether the polyacrylonitrile membrane should be preferred over the polysulphone membrane for CVVH in severe sepsis warrants further experimental and clinical study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 37 publications
0
19
1
2
Order By: Relevance
“…Among the three principles, filtration has been investigated most extensively in the last two decades in the form of a technique increasing filtration volumes (highvolume hemofiltration (HVHF)). Ronco et al conducted a randomized controlled trial (RCT) that compared therapeutic results of RRT in AKI at three different treatment doses (20,35, and 45 mL/kg/h) [15]. Results demonstrated that the survival rate was higher in the 35 and 45 mL/kg/h groups than in the 20 mL/kg/h group.…”
Section: Why Cytokine-adsorbing Hemofilter?mentioning
confidence: 99%
See 2 more Smart Citations
“…Among the three principles, filtration has been investigated most extensively in the last two decades in the form of a technique increasing filtration volumes (highvolume hemofiltration (HVHF)). Ronco et al conducted a randomized controlled trial (RCT) that compared therapeutic results of RRT in AKI at three different treatment doses (20,35, and 45 mL/kg/h) [15]. Results demonstrated that the survival rate was higher in the 35 and 45 mL/kg/h groups than in the 20 mL/kg/h group.…”
Section: Why Cytokine-adsorbing Hemofilter?mentioning
confidence: 99%
“…As the AN69 membrane has a hydrogel structure, adsorption to this membrane is considered to take place not only on the membrane surface but also within the bulk layer, thereby exhibiting a high adsorption capacity. In fact, native AN69 membrane is reported to adsorb a greater amount of humoral mediators such as cytokines compared with PS membrane [35].…”
Section: Pmma Hemofiltermentioning
confidence: 99%
See 1 more Smart Citation
“…AN69 and polysulfone are two of the most commonly used membranes in the ICU to provide CVVH and CVVHD in the last decades [27][28][29][30][31][32][33] . They present different physicochemical properties [31,34] and have been previously compared with diverse purposes [28,31,35] and different conclusions have been reached.…”
Section: Discussionmentioning
confidence: 99%
“…However, these effects that are supposed to be related to the adsorption properties of the membrane are temporary because of saturation phenomenon. 63 Some animal studies assessed HVHF by looking at ultrafiltrate obtained from either healthy donor or septic donor animals and infused into a healthy acceptor animal. The ability for HVHF to remove toxic mediators is suggested when ultrafiltrate obtained from septic animals leads to hemodynamic disturbances or even death in healthy animals.…”
mentioning
confidence: 99%